L‐NAME, a nitric oxide synthase inhibitor, increases the protein expression of both executioner and inhibitor of apoptosis in the placental bed of mid‐to‐late pregnant rats. (27th April 2021) - Ishikawa, Wataru; Kazama, Shugo; Suzuki, Takehito; Yamana, Rei; Miyazaki, Yoko; Tanaka, Kazuaki; Usami, Makoto; Takizawa, Tatsuya
Abstract: The involvement of nitric oxide (NO) signaling in apoptosis was examined in the placental bed of mid‐to‐late pregnant rats. Pregnant rats were treated with l ‐NAME, a nitric oxide synthase inhibitor, by subcutaneous infusion for 48 hours before the examination at day 13.5, 17.5, or 21.5. l ‐NAME induced apoptosis in the placental bed to a limited extent at days 13.5 and 17.5, but not at day 21.5. When the placental bed was examined at day 17.5, the protein expression of both executioner (C‐Cas3) and inhibitor (XIAP) of apoptosis was increased by l ‐NAME, but they did not co‐localized with apoptosis. It was presumed that placental bed apoptosis induced by l ‐NAME is regulated through the expression of both executioner and inhibitor, possibly involving protein S‐nitrosylation.